PEMBENTUKAN PORTOFOLIO SAHAM DENGAN MODEL INDEKS TUNGGAL (SUATU STUDI PADA PERUSAHAAN PERKEBUNAN YANG LISTED DI PT BURSA EFEK INDONESIA) - Pramudianto, Patrick (MABIS, 2012)
Capital market in Indonesia has grown rapidly since 1989, after the government issued various deregulation to spur the growth of the capital market. Individual investors in the equity investment must try to obtain optimal return and reduce risk. Regarding on the purpose, this research used a single index models found by Sharpeto form a stock portfolio. The problem in this research is how to do stock selection in the plantation sector in order to establish optimal stock portfolio with single index model and how much the proportion of funds to be allocated to the portfolio? The research objective is to determine which plantation stocks will form a stock portfolio and how many percentage the allocation of funds to each stock. The research was descriptive form, using secondary data. The data used in this study is quantitative data that individual stock price index, the stock price index and the rate of Bank Indonesia (BI Rate). From the calculation, there are six stocks will establish the optimal stock portfolio. They are PT Smart, Tbk., PTPP London Sumatra Indonesia, Tbk., PT Tunas Baru Lampung, Tbk., PT Sampoerna Agro, Tbk., PT Gozco Plantations, Tbk. and PT Astra Agro Lestari, Tbk. The allocation of funds will be invested by the investor, it is obtained the biggest investment will be invested in stock of PTPP London Sumatra Indonesia, Tbk. amounted to 31.32%, PT Tunas Baru Lampung, Tbk. amounted to 20.20%, PT Sampoerna Agro, Tbk. amounted to 16.59%, PT Smart, Tbk. amounted to 12.09%, PT Gozco Plantations, Tbk. 10.71% and the smallest investment amounted to 9.08%. in stock of PT Astra Agro Lestari, Tbk.